1996
DOI: 10.1074/jbc.271.17.10277
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Physical Interaction between Microsomal Triglyceride Transfer Protein and Apolipoprotein B during the Assembly of ApoB-containing Lipoproteins

Abstract: Microsomal triglyceride (TG) transfer protein (MTP) is an endoplasmic reticulum lumenal protein consisting of a 97-kDa subunit and protein disulfide isomerase. It is believed that MTP delivers TG to nascent apoB molecules during the assembly of lipoprotein particles in the secretory pathway. Although in vitro studies have established the mechanism of TG transfer between donor and acceptor membranes, the mechanism of action of MTP in vivo remains unknown. The present studies were undertaken to examine whether o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 30 publications
(15 reference statements)
6
110
1
Order By: Relevance
“…We further hypothesized that increased levels of apoB synthesis could affect the stability of the MTP protein and, hence, the amount of MTP activity in liver microsomes. Each of these two hypotheses seemed plausible in view of evidence indicating the existence of a direct MTP-apoB interaction within the ER (8,9,11,12) and suggestions that an MTP-apoB complex might play a key role in lipoprotein assembly (12,13). Our data, however, provided no support for either hypothesis.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We further hypothesized that increased levels of apoB synthesis could affect the stability of the MTP protein and, hence, the amount of MTP activity in liver microsomes. Each of these two hypotheses seemed plausible in view of evidence indicating the existence of a direct MTP-apoB interaction within the ER (8,9,11,12) and suggestions that an MTP-apoB complex might play a key role in lipoprotein assembly (12,13). Our data, however, provided no support for either hypothesis.…”
Section: Discussioncontrasting
confidence: 56%
“…1A). Recent studies have suggested that apoB and MTP bind to each other during lipoprotein assembly (8,11,12). We hypothesized that overexpression of human apoB might conceivably lead to an increased number of those interactions, potentially stabilizing MTP within the ER and leading to increased amounts of MTP activity in hepatic microsomes.…”
Section: Mtp Activity and Protein Levels In Liver Extracts From Diffementioning
confidence: 99%
“…Despite the fact that MTP is characterized in great detail, relatively little is known about the molecular details of the role of this protein in the assembly of the lipoprotein. An interaction with apoB has been demonstrated (23,24) and suggested to involve the N-terminal globular domain of apoB, which is needed for the action of MTP (25,26). In a recent study, we demonstrated that MTP is necessary for the early events in the assembly of endogenous apoB-48 VLDL in the McA-RH7777 cells, but does not appear to be essential for the step in which the major amount of lipids was added to the particle (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a physical interaction between MTP and the amino-terminal domain of apoB (20,21). It is possible therefore that discrete disulfidebonded loops within this domain form a critical recognition site for the initial interaction of MTP with the nascent apoB polypeptide chain.…”
Section: Cys Pairs 2 and 4 Are Essential For The Assembly And Secretimentioning
confidence: 99%